Общие формулы:
a(n) = a1 + d(n-1)
S(n) = (a1 + a(n))*n/2 = (2a1 + d(n-1))*n/2
1) a1 = 65; d = - 2
a32 = a1 + 31d = 65 + 31(-2) = 65 - 62 = 3
a40 = a1 + 39d = 65 + 39(-2) = 65 - 78 = - 13
2) a1 = 42; d = 34 - 42 = - 8
a24 = a1 + 23d = 42 + 23(-8) = - 142
S(24) = (a1 + a24)*24/2 = (42 - 142)*12 = - 100*12 = - 1200
3) b(n) = 2n - 5; b1 = - 3; b2 = - 1; d = 2; b80 = 155
S(80) = (a1 + a80)*80/2 = (-3+155)*40 = 152*40 = 6080
4) a1 = - 2,25; a11 = 10,25; n = 11
Найдем разность прогрессии d.
a11 = a1 + 10d
10,25 = - 2,25 + 10d
d = (10,25+2,25)/10 = 12,5/10 = 1,25
Проверим, при каком n получится 6,5.
a(n) = a1 + d(n-1)
6,5 = - 2,25 + 1,25*n - 1,25 = 1,25*n - 3,5
1,25*n = 6,5 + 3,5 = 10
n = 10/1,25 = 8
n целое, значит, 6,5 действительно член этой прогрессии.
В решении.
Объяснение:
1)
а) (5a² + ab)³ = (5a²)³ + 3*(5a²)²*ab + 3*5a²*(ab)² + (ab)³ =
= 125a⁶ + 75a⁵b + 15a⁴b + a³b³;
б) (x⁴ - y⁴)³ = (x⁴)³ - 3*(x⁴)²*y⁴ + 3*x⁴*(y⁴)² - (y⁴)³ =
= x¹² - 3x⁸y⁴ + 3x⁴y⁸ - y¹²;
в) (3a² - 1/2 a)³ = (3a²)³ - 3*(3a²)²*1/2 a + 3*3a²*(1/2 a)² - (1/2 a)³ =
= 27a⁶ - 13,5a⁵ + 2,25a⁴ - 1/8 a³;
г) (x¹² + 2y²)³ = (x¹²)³ + 3*(x¹²)²*2y² + 3*x¹²*(2y²)² + (2y²)³ =
= x³⁶ + 6x²⁴y² + 12x¹²y⁴ + 8y⁶;
д) (10y¹⁰ - 3z³)³ = (10y¹⁰)³ - 3*(10y¹⁰)²*3z³ + 3*10y¹⁰*(3z³)² - (3z³)³ =
= 1000y³⁰ - 900y²⁰z³ + 270y¹⁰z⁶ - 27z⁹;
е) (-2/3 ab² + 3/2 b)³
= (-2/3 ab²)³ + 3*(-2/3 ab²)²*3/2 b + 3*(-2/3ab²)*(3/2 b)² + (3/2 b)³ =
= -8/27a³b⁶ + 2a²b⁵ - 4,5ab⁴ + 27/8 b³.
2) Вычислить:
а) 5,1³ = 132,651; б) 9,9³ = 970,299;
в) 1,2³ = 1,728; г) 0,8² = 0,64.